ECOLOGICAL-EPIZOOTOLOGICAL SIGNIFICANCE OF LARVAL DEVELOPMENT OF CAUSES OF NEMATODOTIC DISEASES (British Journal of Global Ecology and Sustainable Development, 2023)
The manifestation of the resistance of eggs and larvae of strongylates of the digestive tract and respiratory tract of sheep and goats was studied using the examples of marshallagia, nematodes, dictauls to adverse environmental factors. It has been established that eggs and larvae of strongylates developing according to the semi-closed type are more resistant to an aquatic environment containing 3.0; 4.0; 5.0 and 6.0% NaCl than in strongylates whose larvae develop according to the open and semi-open types.